BOARD SIZE AND COST EFFICIENCY IN ISLAMIC BANKS IN INDONESIA - Lalang Mahesky; Samsul Rosadi (International Conference on Economics, Management, Business, and Accounting, 2024)
This study aims to analyze the board size's impact on cost efficiency in the context of Islamic banks in Indonesia. Board size involves the composition of the board of commissioners, board of directors, and the sharia supervisory board, all of which play vital roles in guiding and overseeing a bank's activities. In this research, we take an empirical approach, using linear regression analysis to examine the influence of the board size of commissioners, directors, and the sharia supervisory board on cost efficiency through the use of a Fixed Effect Model with software Stata 17. Panel data was collected from Islamic banks in Indonesia for the period 2015-2022. The analysis results indicate that the size of the Board of Commissioners does not have a significant impact on cost efficiency. Meanwhile, the size of the Board of Directors and the size of the Sharia Supervisory Board have a negative effect on the cost efficiency of Islamic banks.